“Did you shoot the girl in the street?” – On the Digital Seriality of The Walking Dead - Sulimma, Maria (Eludamos: Journal for Computer Game Culture, 2014)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false DE X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><span style="font-size: 12.0pt; line-height: 107%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: DE; mso-bidi-language: AR-SA;" lang="EN-US">With the Walking Dead game series, I tackle a very extensive and rich material in this paper and show how digital seriality accounts for very specific practices of production, reception, as well as game-play. The first section focuses on the inter-ludic seriality of the game’s release and structuring as reminiscent of TV series (seasons, episodes, “previously on”) as well as the comic book-aesthetic and transmedia storytelling as para-ludic seriality. The game series employs different strategies of transmedia storytelling to position the game within the crossmedia franchise of The Walking Dead. Besides inviting comparison of the different protagonists or “cameos” by established characters, the game series also explores themes like parenting/childhood or the handling of injury in a media specific manner. Gender and race play a particular role concerning the theme of parenting. The first section of the paper touches on intra-ludic seriality and the importance of relating game experiences to a collective of other gamers to provide a self-aware pleasure in variation as well as the game’s mechanics. In the game’s playing statistics as well as in “meta-moments”, practices of individuality and collectivity are enabled through the game’s operational aesthetic as well as gamers’ serial appreciation of variation as a narrative outcome of the choices made.